Can a supportive supervisor be a treasure for teachers? A multilevel analysis of the relationship between perceived supervisor support, work engagement, and burnout - Uslukaya, Alper; Demirtas, Zulfu (Wiley, 2023)
In this study, we examined the relationships between perceived supervisor support, work engagement, and burnout levels of teachers by using multilevel analysis. We assumed that a high level of perceived supervisor support would relate positively to work engagement but negatively to burnout. We also suggested that work engagement would mediate the relationship between perceived supervisor support and burnout. The participants of the study consisted of 796 teachers from 87 schools located in the center of Elazig province in eastern Turkey. According to multilevel structural equation modeling analysis, we found that perceived supervisor support is positively related to work engagement but negatively to burnout at the teacher and school levels. We carried out a series of Sobel tests for multilevel mediation analyses and identified the presence of a mediating role in the relationship between perceived supervisor support and burnout at both levels of work engagement in general. In conclusion, this study indicates that perceived supervisor support can be a significant resource for teachers' well-being.
Keywords: absroption; burnout; dedication; percieved supervisor support; vigor; work engagement